How Does a Covenantal Approach to Developing Organizational Leadership Affect Innovation?. Issue 1 (May 2016) - Fischer, Kahlib J.; Schultz, Jonathan
Abstract : As organizations grow, they become more hierarchical and less adaptive; thus, innovation and intrapreneurship suffer. A covenantal approach to organizational behavior and leadership can facilitate organizational flexibility and adaptability to foster further innovation by engendering empowerment and deeper, more meaningful engagement among leadership and followers. A covenant is a morally informed agreement among two or more parties who commit to care for one another and protect one another's rights. Noncentralization, participative decision making, active dialog and big picture thinking are all encouraged by a covenantal approach, which in turn helps to foster innovation.